The processes associated with lipid peroxidation in human embryonic lung fibroblasts, treated with polycyclic aromatic hydrocarbons and organic extract from particulate matter - Rossner, Pavel; Libalova, Helena; Cervena, Tereza; Vrbova, Kristyna; Elzeinova, Fatima; Milcova, Alena; Rossnerova, Andrea; Novakova, Zuzana; Ciganek, Miroslav; Pokorna, Michaela; Ambroz, Antonin; Topinka, Jan (Mutagenesis, 2019)
Polycyclic aromatic hydrocarbons (PAHs) may cause lipid peroxidation via reactive oxygen species generation. 15-F2t-isoprostane (IsoP), an oxidative stress marker, is formed from arachidonic acid (AA) by a free-radical induced oxidation. AA may also be converted to prostaglandins (PG) by prostaglandin-endoperoxide synthase (PTGS) induced by NF-κB. We treated human embryonic lung fibroblasts (HEL12469) with benzo[a]pyrene (B[a]P), 3-nitrobenzanthrone (3-NBA) and extractable organic matter (EOM) from ambient air particulate matter <2.5 µm for 4 and 24 h. B[a]P and 3-NBA induced expression of PAH metabolising, but not antioxidant enzymes. The concentrations of IsoP decreased, whereas the levels of AA tended to increase. Although the activity of NF-κB was not detected, the tested compounds affected the expression of prostaglandin-endoperoxide synthase 2 (PTGS2). The levels of prostaglandin E2 (PGE2) decreased following exposure to B[a]P, whereas 3-NBA exposure tended to increase PGE2 concentration. A distinct response was observed after EOM exposure: expression of PAH-metabolising enzymes was induced, IsoP levels increased after 24-h treatment but AA concentration was not affected. The activity of NF-κB increased after both exposure periods, and a significant induction of PTGS2 expression was found following 4-h treatment. Similarly to PAHs, the EOM exposure was associated with a decrease of PGE2 levels. In summary, exposure to PAHs with low pro-oxidant potential results in a decrease of IsoP levels implying 'antioxidant' properties. For such compounds, IsoP may not be a suitable marker of lipid peroxidation.
Keywords: polycyklické aromatické uhlovodíky; Oxidative Stress; reaktivní formy kyslíku; oxidační stres; pevné částice; Humans; aromatické hydroxylasy; cyklooxygenasa 2; Cyclooxygenase 2; peroxidace lipidů; Aryl Hydrocarbon Hydroxylases; Lung; lidé; Polycyclic Aromatic Hydrocarbons; Air Pollutants; Cells, Cultured; plíce; Arachidonic Acid; Dinoprostone; Reactive Oxygen Species; Particulate Matter; Dinoprost; látky znečišťující vzduch; benz(a)anthraceny; kultivované buňky; Benzo(a)pyrene; fibroblasty; NF-kappa B; dinoproston; Benz(a)Anthracenes; benzopyren; kyselina arachidonová; dinoprost; Lipid Peroxidation; Fibroblasts